In Memoriam, Norman Borlaug - Sarquís-Ramírez, Jorge Isaac (International Journal of Bio-resource and Stress Management, 2010)
The article briefly highlights the profile of great Norman Ernest Borlaug (1914-2009) who received Nobel Peace Prize in 1970 for his outstanding contribution in world food production. A Norwegian in origin NE Borlaug was born in Iowa and served the country of Mexico for around 40 years. A PhD in plant pathology and genetics, Borlaug was Director of International Wheat Improvement Program at International Maize and Wheat Improvement Center (CIMMYT) in Mexico. Though criticized and opposed for his work several times, Borlaug was also reckoned as Father of Green Revolution who started a new era of agriculture—the modern agriculture. Dr Borlaug established the World Food Prize in 1986—an award in recognition of people for their contribution to world food production. This prize in food and agriculture has acquired a high prestige similar to that of the Nobel Prize. ‘Aim at the stars’, he advised his students, ‘knowing that you will never get one, but some stardust may fall upon you’. The author had a rare privilege to meet such a great personality who spent his entire life battling with hunger.